Validation of the general Framingham Risk Score (FRS), SCORE2, revised PCE and WHO CVD risk scores in an Asian population - Sazzli, Shahlan Kasim; Nurulain, Ibrahim; Sorayya, Malek; Khairul, Shafiq Ibrahim; Muhammad Firdaus, Aziz; Song, Cheen; Chia, Yook Chin *; Anis, Safura Ramli; Negishi, Kazuaki; Nafiza, Mat Nasir (Elsevier, 2023)
Background: Cardiovascular risk prediction models incorporate myriad CVD risk factors. Current prediction models are developed from non-Asian populations, and their utility in other parts of the world is unknown. We validated and compared the performance of CVD risk prediction models in an Asian population.